Scythian bronze cauldrons from the National Museum of History of Moldova - Denis Topal (Tyragetia, 2020)
Bronze cauldrons of the Scythian time are a rather rare find in the Northern Black Sea region, especially on its western borders. Therefore, those few items found on the territory of the Republic of Moldova occupy a worthy place in the collection of the National Museum of History of Moldova (NMHM). In particular, at the moment in the main archaeological exhibition two bronze cauldrons are displayed, which were discovered near the village of Nikolskoe in 1988 in burial mounds no. 14 and no. 15. In addition, already in 2020, two bronze cauldrons without any accompanying documents were found in the collection of NMHM; however, they were visually identified as coming from various excavations in the Low Dniester region: from the burial mound no. 45 near Dubossary and burial mound no. 1 near the Răscăieţii Noi village. Scythian bronze cauldrons in the west area are concentrated in three main regions: Bukovina Podolia (Iacobeni, Ivane-Puste, Shvaikivtsy), the Lower Dniester (Răscăieţii Noi, Nikolskoe, Dubossary, Coiburciu), and the Lower Danube (Ograda, Castelu, Scorţaru Vechi, Mresnota Mogyla, Ostrovnoe). Some Scythian cauldrons have no reliable archaeological context. Nevertheless, in combination with the same “stray” finds like the Scythian statues, the finds of Scythian cauldrons mark the Scythian presence, most likely, not earlier than the late 6th century or even the turn of the 6th-5th centuries BC. There is a significant chronological difference between the northern (forest-steppe, Bukovina-Podolia) group of cauldrons and the southern (steppe, Lower Danube-Lower Dniester). At the same time, a chronological priority is characteristic of the first, where the cauldrons are known since the middle of the 7th century BC. Bronze cauldrons (with their carriers) penetrate the steppe region 150-200 years later, as well as the “military” burials that appear in the western steppe regions no earlier than the middle of the 5th century BC. Most of the burials with cauldrons (and, apparently, the stray finds) are dated back to the second half of the 5th century BC. Then, at the early 4th century BC their quantity is reduced and after the first quarter of the 4th century BC they will completely disappear from the cultural practice of the population of the steppes of the North-Western Black Sea region.